Aproveitamento do carvão ativado obtido da casca de castanha de caju no processo de tratamento de águas cinzas - Maia, Danielma Silva (Universidade Federal do Tocantins, 2021)
This study aims to develop technical knowledge about cashew nut shell, presenting and characterizing the biochar from this biomass, generated through the pyrolysis process. So that it can be verified the potential of using activated carbon in the adsorption of pollutants present in gray water. Through immediate and elemental analysis, the characterization of this biomass and activated carbon obtained through the pyrolysis of cashew nut shell in a fixed bed reactor at temperatures ranging from 400ºC to 600ºC and heating rate of 15ºC was carried out /min at 25°C/min. The fixed bed reactor is made of stainless steel material, which is 100 cm long and has an external diameter of 10 cm, is heated by a bipartite reclining oven and operates in a batch regime. The study of coal was complemented with thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) analysis. The mass yield of coal ranged from 33.10% to 36.10% when subjected to a temperature of 500°C and heating rate at 20°C/min, which indicates a favorable yield to the values defined for these central point variables in the experimental planning . Regarding the behavior of activated charcoal from cashew nut shells in the adsorption process of contaminants from gray water through the methylene blue index adsorption test, the experiment showed that, with low mass and high concentration dye, its adsorption capacity becomes more efficient. In addition, the treatment of gray water with the use of biochar, was developed first with the step of decantation, sedimentation and flocculation and later with the step of filtering this effluent using activated carbon and sand. The treatment of greywater in these steps was shown to be appropriate, as it removes COD, volatile solids, soluble orthophosphate, residual chlorine and ammonia in percentages above 80% and high removal of the turbidity parameter (above 90%).